Reuma.pt contribution to the knowledge of immune-mediated systemic rheumatic diseases - Santos, Maria José (2017)
Patient registries are key instruments aimed at a better understanding of the natural history of diseases, at assessing the effectiveness of therapeutic interventions, as well as identifying rare events or outcomes that are not captured in clinical trials. However, the potential of registries goes far beyond these aspects. For example, registries promote the standardization of clinical practice, can also provide information on domains that are not routinely collected in clinical practice and can support decision-making. Being aware of the importance of registries, the Portuguese Society of Rheumatology developed the Rheumatic Diseases Portuguese Register- Reuma.pt - which proved to be an innovative ins - trument essential to a better understanding of systemic immune-mediated rheumatic diseases. Objective: To describe the contribution of Reuma.pt to the knowledge of systemic immune-mediated rheumatic diseases. Results: Reuma.pt is widely implemented, with 77 centres actively contributing to the recruitment and follow- -up of patients. Reuma.pt follows in a standardized way patients with the following systemic inflam matory rheumatic diseases: rheumatoid arthritis (n=6.218), pso - riatic arthritis (n=1.498), spondyloarthritis (n=2.529), juvenile idiopathic arthritis (n =1.561), auto-inflammatory syndromes (n=122), systemic lupus erythematosus (n =1.718), systemic sclerosis (n=180) and vasculitis (n=221). This platform is intended for use as an electronic medical record, provides standardized assessment of patients and support to the clinical decision, thereby contributing to a better quality of care of rheumatic patients. The research based on Reuma.pt identified genetic determinants of susceptibility and response to therapy, characterized in detail systemic rheumatic diseases and their long-term impact, critically appraised the performance of instruments for monitoring the disease acti - vity, established the effectiveness and safety of biolo gic therapies and identified predictors of response, and proactively engaged patients in the management of their disease. Conclusion: Reuma.pt is an innovative tool, widely established in the country that contributes to a clinical practice of excellence and simultaneously to increase the knowledge of systemic immune-mediated rheuma - tic diseases. Additionally, Reuma.pt fosters patients' participation in the management of the disease.